Optimization of nanoemulsion formulation containing phenytoin - Yap, Mavin Chong Yang (2017)
Epilepsy is a Central Nervous System (CNS) disease caused by abnormal neuron signalling causing repeated seizures. CNS is protected by a barrier known as blood-brain barrier (BBB). The selective membrane on the BBB which only allow small lipophilic particle to pass through complicates the penetration of antiepileptic drugs. Phenytoin is a classic antiepileptic drug (AED) listed on the World Health Organization’s List of Essential Medicines, which exhibits potent therapeutic efficacy in controlling seizure attacks thus signifying its importance in a basic healthcare system. However, due to poor solubility and bioavailability of phenytoin, large dosage had to be given in its salt form (phenytoin sodium) to reach therapeutic concentration with numerous side effects. Hence, incorporating phenytoin in a nanocarrier would increase its bioavailability while minimizing the dosage required with reduced side effects. From the formulation study, it was discovered that phenytoin could only be retained in alkali solution. Therefore to address the solubility issue of phenytoin, a two-step method based on the pH solubility profile of phenytoin was used to formulate phenytoin into the nanoemulsion. First step involves the formulation of blank nanoemulsion (without phenytoin) through magnetic stirring followed by high shear homogenization. Second step involves the incorporation of phenytoin onto the nanocarrier by adjusting pH of blank nanoemulsion to alkali condition. Incorporation of phenytoin was confirmed through Transmission Electron Microscopy (TEM) which showed the position of phenytoin on the surface of oil droplets. Mixture Experimental Design (MED) and Artificial Neural Network (ANN) were employed to optimize the composition of phenytoin-loaded nanoemulsion. Effects of isopropyl myristate (3.00-6.00%, wt%), Tween 80:85 (1.50-3.00% wt%), glycerol (4.00-7.00%, wt%), and water (84.00- 91.50%, wt%) on the droplet size of nanoemulsion were investigated. The optimum formulation obtained from the mathematical model with desirable criteria were 3.00% isopropyl myristate, 2.04% Tween 80:85, 7.00% glycerol and 87.96% water. Based on the optimum formulation from MED, the predicted response value for droplet size was 99.58 nm, while the predicted value from ANN was 98.27 nm, which showed in excellent agreement with the actual value obtained from the experiment which was 98.69 nm. Toxicity comparison between Dilantin (parenteral phenytoin sodium) and phenytoin-loaded nanoemulsion showed that the nanoemulsion to be four times less toxic compared to Dilantin towards Vero (kidney) cells. Stability evaluation based on the droplet size for three months showed that the droplet size remained in nano-size with less than 5% change. Entrapment study showed that more than 95% of phenytoin was encapsulated throughout 3 months storage. In conclusion, the nanoemulsion formulation is a safer and promising vehicle for the delivery of phenytoin through intravenous route.